Bank stability and the allocation of liquidity in the banking system - Hendrik Hakenes; Eva Schiephake (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2017)
The fragility of financial institutions to panic runs depends on their liquidity base: the short term funds available to banks for investment regardless of the withdrawal option available to customers. Institutions that are able to offer higher yield curves are able to lure the liquidity base away from their competitors. Using the standard global games approach, we show that banks that attract a high liquidity base are less prone to panic runs, but the stability of the residual banks decreases.
Keywords: G21; G28; H23; 330